Transcatheter Aortic Valve Replacement (TAVR) in Patients with Paradoxical Low-Flow Low-Gradient Aortic Stenosis. Issue 4 (3rd July 2020) - Thakker, Prashanth; Husaini, Mustafa; Thangam, Manoj; Lindman, Brian; Maniar, Hersh; Quader, Nishath; Melby, Spencer; Sintek, Marc; Kachroo, Puja; Lasala, John; Zajarias, Alan
ABSTRACT: Background: Aortic valve replacement is recommended in symptomatic patients with severe aortic stenosis (AS) or asymptomatic with reduced left ventricular ejection fraction (LVEF). The treatment algorithm of patients with paradoxical low-flow (pLF-LG) AS is not well defined. The purpose of this study is to examine the efficacy and outcomes of TAVR in patients with pLF-LG AS at our institution. Methods: From 2008 to 2017, we retrospectively analyzed patients who underwent TAVR with an LVEF > 50% and stratified into 4 groups based on gradient and stroke volume index. The groups were normal flow, high gradient (NFHG), normal flow, low gradient (NFLG), low flow, high gradient (LFHG), and paradoxical low flow, low gradient (pLF-LG). Baseline, procedural characteristics, post-procedure, 30-day, and 12-month endpoints were obtained. Our primary endpoints included all-cause mortality and major adverse cardiac and cerebrovascular events (MACCE) at post-procedure, 30 days, and 1 year. Results: Groups were NF-HG (n = 145), NF-LG (n = 81), LF-HG (n = 97), and pLF-LG (n = 75). There was an increased prevalence of pacemakers in the pLF-LG group ( p = 0.01) and a significant difference in the prevalence of atrial fibrillation (AF) ( p = 0.01). No difference in post-procedure, 30-day, and 12-month all-cause mortality and MACCE was noted. All patients demonstrated symptomatic improvement as measured by New York Heart Association (NYHA) class at 30 days and 12 months ( p < 0.0001) Conclusion: When compared to patients with normal flow and high gradients, patients with pLF-LG treated with TAVR had similar procedural complications and 30-day and 1-year mortality with improvement in symptom profile. Once identified as symptomatic, patients with pLF-LG should undergo valve replacement.